PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN MUTU PROSES PEMBELAJARAN GURU DI SEKOLAH DASAR - Dewi Maria; Asep Mulyana; Sarah Adawiyah; Hima Alawiyah; Alvina Putri Sukmana; Dinny Mardiana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Twenty-first-century education requires learning processes that foster students' critical thinking, creativity, communication, and collaboration skills. However, learning activities in elementary schools are still often teacher-centered, resulting in limited student participation during the learning process. One learning model that can address this issue is Project Based Learning (PjBL). This study aims to describe the implementation of the Project Based Learning (PjBL) model and its impact on the quality of learning in elementary schools. This study employed a qualitative approach using a descriptive method. The research subjects consisted of the principal, teachers, and students. Data were collected through observation, interviews, and documentation. The findings revealed that the implementation of PjBL was carried out in accordance with the stages of project-based learning. Based on observations, interviews, and documentation, the implementation of PjBL encouraged students to become more active in discussions, collaboration, and project completion activities. In addition, teachers became more creative in designing instructional materials, selecting learning media, and implementing student-centered learning. Although several challenges were identified, including limited time and supporting facilities, the implementation of PjBL had a positive impact on the quality of learning in elementary schools by creating a more active, interactive, and meaningful learning environment.